A COMPARATIVE STUDY ON SOME PROPERTIES AND OXIDATION STABILITY DURING STORAGE OF BUTTER PRODUCED FROM DIFFERENT ANIMALS' MILK - ÇAKMAKÇI, Songül; TAHMAS KAHYAOĞLU, Deren (Association of Food Technology, Turkey, 2018)
In this study, butter produced from cow, sheep and goat cream and was examined during a 90 day storage period at 4°C. A total of 42 samples produced and were analysed at 1st, 15th, 30th, 45th, 60th, 75th and 90th days. It was found that butter type and storage period had significant effect on the pH value, titratable acidity, acid value, fat constants, peroxide and thiobarbituric acid values, β-carotene and vitamin A amounts of the butter samples. The pH value, iodine number, b value and vitamin A amounts decreased during the storage in all the types of butter, whereas titratable acidity, acid value, Reichert-Meissl, Polenske and saponification numbers and oxidation increased. β-carotene was detected only in butter produced from cow milk creams which decreased during storage. Sensory analysis points decreased in all the butter samples during the storage the highest point belonging to the butter produced from cows’ milk.
Keywords: 2. Zero hunger